2008
DOI: 10.1097/mlg.0b013e31817d7546
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Pulse Dye Laser in the Treatment of Vocal Fold Scar: A Preliminary Study

Abstract: PDL is a safe and potentially promising treatment for established vocal fold scar. Subjectively, no patients were worse and 10 of 11 patients reported improved voice. There was improvement in the VHI, acoustic measures of shimmer and jitter, and stroboscopy findings. Further study using this approach in a larger cohort seems to be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 18 publications
0
41
0
1
Order By: Relevance
“…These data are neither consistent with our clinical observations nor previously published data. 14 As noted in the Methods section, data regarding the specific laser settings were not included in the analysis. Although these data may be important from a documentation standpoint, the complexities of the laser-tissue interaction and uncertainties regarding the actual energy delivered to the tissue make it impossible to rely on settings as a guide to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…These data are neither consistent with our clinical observations nor previously published data. 14 As noted in the Methods section, data regarding the specific laser settings were not included in the analysis. Although these data may be important from a documentation standpoint, the complexities of the laser-tissue interaction and uncertainties regarding the actual energy delivered to the tissue make it impossible to rely on settings as a guide to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, postradiation scar only accounted for 18% of the study population, and results of the patients who received radiation were not reported separately. 40 Vocal fold augmentation with injection laryngoplasty or medialization thyroplasty has been used to improve glottic competency and reduce the subglottic pressure required to drive phonation. 12 Importantly, augmentation does not directly address vocal fold scar and does not improve the vibratory capacity of the vocal folds.…”
Section: Surgical Treatment Optionsmentioning
confidence: 99%
“…Disruption of the vocal fold ECM, particularly due to inflammatory and fibrotic processes, can result in altered tissue viscoelasticity, oscillatory function and voice. Even certain therapeutic interventions to treat or remove diseased tissue can result in residual scarring and poor voice outcomes (5,6). As a result, minimally invasive treatments that result in maximum preservation of ECM structure and function are highly desirable in the treatment of vocal fold pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Its application to epithelial lesions is based on the observation that the delivery of PDL energy can result in cleavage of the epithelial cell layer from the underlying superficial LP, hypothesized as due to the denaturation of basement membrane linking proteins (16). In addition to these two therapeutic indications, recent clinical evidence suggests that the PDL may be useful in the treatment of disordered ECM in patients with chronic vocal fold scar (5), although the mechanism by which PDL irradiation might improve ECM structure and function in this population is unknown.…”
Section: Introductionmentioning
confidence: 99%